Leadership Practices by Heads of Institution of Empowering Teachers on Competence-Based Education Sustainability in Public Junior School: A Case of Kisii County, Kenya - Rosalia Bosibori Nyamwamu; Justina S. Ndaita; Benard Omenge Nyatuka (Research Journal of Education, Teaching and Curriculum Studies, 2026)
This study aimed at investigating Leadership Practices by Heads of Institution of Empowering Teachers on Competence-Based Education (CBE) Sustainability in Public Junior School. Curriculum reform is vital in ensuring that education system meets societal demands. The study adopted a census technique for the Sub-County Quality Assurance and Standards Officers (SCQASOs), involving all 11 officers since the population was small, accessible, and suitable for eliminating sampling error while achieving the desired level of precision. The Yamane (1967) simplified formula for finite populations was used to determine the sample sizes for Heads of Institutions (HOIs) and JS Teachers at a 7% precision level. Yamane (1967) simplified formula was used because the population was known. For HOIs, with a total population of 686, the sample size was calculated as n = 157 distributed proportionately to all sub-counties. As for JS teachers, with a total population of 1,925, the sample size was calculated as n = 185 and the sample were proportionally distributed across the sub-counties. Overly, the sample comprised of 11 (SCQASOs), 157 HOIs and 185 Junior School teachers, hence, a total sample of 353. The study employed a mixed-methods research design, which integrates both quantitative and qualitative approaches to provide a more comprehensive understanding of the research problem. Results showed high mean scores for teacher empowerment (M = 4.10, Std.Dev. = 0.54). The study therefore, recommends continuous empowerment of teachers and learners to enhance sustained CBE implementation.